Applicability of ring‐on‐disc and pin‐on‐plate test methods for Cu–steel and Al–steel systems for large area conformal contacts. (21st May 2012) - Pondicherry, Kartik S.; Grün, Florian; Gódor, István; Bertram, Rich; Offenbecher, Martin
ABSTRACT This study compares two methods for model scale testing of ferrous/non‐ferrous tribocouples under large area conformal contact condition, the kind existing in engine components such as journal bearings. Results show that the ring‐on‐disc method is better suited to visualise the performance of such tribosystems compared with the pin‐on‐plate method. The former offers greater sensitivity to minor changes in coefficient of friction and contact potential and is able to determine the thermal stability of the tribosystem under given conditions. Post‐test surface characterisation revealed protective phosphorus‐rich tribofilms on the surface of the steel counterparts from both test methods. Copyright © 2012 John Wiley & Sons, Ltd.